ACFARvideo
The mission of the Africa Centre for Apologetics Research is rooted in Jesus’ “Great Commission” (Mt. 28:18–20), in which He commands us to disciple the nations. First, we are tasked with equipping God’s people for discernment—helping them distinguish scripturally between truth and error, good and evil, darkness and light. Spiritual counterfeits thrive in the absence of “the mature, who because of practice have their senses trained to discern good and evil” (Heb. 5:14). Second, we seek to train believers for the defence of the faith (Jude 3–4). This command requires us to “earnestly contend” for that faith in the face of opposition—simply and reasonably, with sincerity and zeal, humbly speaking the truth that God has revealed. Third, we seek to mobilize Christians for the neglected but essential task of cult evangelism. This means compassionately helping those entrapped in cultic groups to know Jesus Christ as the true and living God and grasp the hope that only He can offer.
free